Crystal structure of panduratin A: (l′RS, 2′SR, 6′RS)-(2, 6-Dihydroxy-4-methoxyphenyl)- [3′-methyl-2′-(3″-methylbut-2″-enyl)- 6′-phenylcyclohex-3′-enyl]methanone - Orasa Pancharoen (2018)
Single-crystal X-ray structure determination of the title compound, C26H30O4, confirms the stoichiometry, connectivity and stereochemistry recently assigned spectroscopically. Crystals are monoclinic, P21/n, a 10.140(5), b 24.85(1), c 9.415(4) Å, β 90.69(4)°, Z 4; the structure was refined to a residual of 0.055 for 1701 ‘observed’ independent reflections. © 1984 ASEG.